FEATURES OF DEVELOPMENT OF LIGHT INDUSTRY IN UZBEKISTAN - Shahlo Tursumatova; Shaxzoda Erkinova (American Journals Publishing, 2023)
The purpose of the article is to review the foreign practice in the development of the light industry and to determine its features. The head of state defined the problem of ensuring the competitiveness of our country's enterprises as the most important direction of the political strategy. The modern international policy of Uzbekistan is aimed at integrating the country into the world economic community. Ensuring the competitiveness of enterprises in the conditions of economic globalization is a factor that determines their security and the economic security of the state in general. The republic's membership in the WTO (World Trade Organization) in the near future requires the development of competitive industrial production, including light industry.
Keywords: Light industry, development, practice, production, economy, tools, industry.